PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM - Mukti, Muhi; Maesaroh, Maesaroh; Meydenvy, Gisty (The Asia Pacific Journal Of Management Studies, 2023)
The objectives of this study are (1) to determine the effect of Debt To Equity Ratio (DER) on Stock Prices in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 Period, (2) to determine the Return On Equity (ROE) Towards Share Prices in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 Period. The method used in this research is descriptive and quantitative research methods. The sampling technique used by purposive sampling is a sample selected using certain considerations in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period which can be accessed or downloaded directly on the official Stock Exchange website. Indonesia (IDX) www.idx.co.id and https://finance.yahoo.com. Testing of this research was carried out using the Classical Assumption Test, then analyzed with the Correlation Test and Multiple Linear Regression Test using the SPSS V.20 program. Conclusion Debt To Equity Ratio (DER) has an effect on Stock Prices, Return On Equity (ROE) has no effect on Stock Prices, Debt To Equity Ratio (DER), Return On Equity (ROE), Stock Prices occur simultaneously have an effect